The Impact of Andean Cultural Values and Idiosyncrasy on Associative Models for Small Farmers in Peru - Morales Tristán, Oswaldo (2008)
Descargue el texto completo en el repositorio institucional de la Waseda University: http://hdl.handle.net/2065/34695